Long-term patient and kidney survival after coronary artery bypass grafting, percutaneous coronary intervention, or medical therapy for patients with chronic kidney disease: a propensity-matched cohort study. Issue 1 (January 2018) - Vuurmans, Tycho; Er, Lee; Sirker, Alexander; Djurdjev, Ognjenka; Simkus, Gerald; Levin, Adeera
Abstract : Background: Revascularization in patients with chronic kidney disease (CKD) and coronary artery disease (CAD) is often deferred because of concern over progression of renal failure. Hypothesis: Revascularization with either coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) leads to progression of renal failure, but improves survival compared with medical therapy in patients with CKD. Patients and methods: Linkages between the British Columbia Cardiac Registry and the British Columbia Renal Registry of patients with established CAD and CKD who underwent CABG, PCI, or were treated medically were propensity matched. Overall patient survival was analyzed using a Cox proportional hazard model. Primary renal outcomes, defined as patients requiring long-term dialysis or progressive loss in kidney function, were analyzed using a competing risk approach. Results: On the basis of the matched cohort, the risk of renal outcome in the first three months was the highest in the CABG group, but comparable between the PCI and the medical group (estimated probability at 3 months: 12.7% for CABG, 5.4% for PCI, 4.4% for medical; P <0.01). The estimated probability for the renal outcome at 24 months was similar across the groups: 37.9% for CABG, 37.6% for PCI, and 35.2% for medical therapy ( P =0.62). The mortality risk at 24 months was lower for CABG (3.9%) compared with PCI (14.5%) or medical therapy (16.4%) ( P <0.01). Conclusion: In patients with CAD and CKD who undergo the current practice of CABG, PCI, or are treated with medical therapy, progression of renal failure is higher in the first 3 months for CABG, but similar for all groups at 24 months. The 2-year mortality is lower in patients treated with CABG compared with PCI or medical therapy. Abstract : Supplemental Digital Content is available in the text.